Podocytes and Proteinuria in ANCA-Associated Glomerulonephritis: A Case-Control Study - van Daalen, Emma E.; Neeskens, Peter; Zandbergen, Malu; Harper, Lorraine; Karras, Alexandre; Vaglio, Augusto; de Zoysa, Janak; Bruijn, Jan A.; Bajema, Ingeborg M. (Frontiers in Immunology, 2019)
Proteinuria has been identified as prognosticator of renal outcome in patients with ANCA-associated glomerulonephritis, but whether proteinuria is related to podocyte abnormalities in these patients is largely unknown. We here investigate podocyte foot process width and number of podocytes positive for the podocyte marker WT-1 in diagnostic renal biopsies of 25 Caucasian patients with ANCA-associated glomerulonephritis in relation to proteinuria. Control tissue was used from pre-transplantation donor kidney biopsies. Proteinuria at 10 weeks follow-up correlated significantly with foot process width (P = 0.04). Biopsies with foot process width ≥600 nm belonged more often to the crescentic or mixed class, whereas biopsies with a foot process width <600 nm were most often categorized as focal class (P = 0.03). The mean number of podocytes based upon expression of WT-1 was significantly lower in patients compared to controls (15 versus 34 podocytes per glomerulus; P < 0.0001). The significant decrease in expression of the podocyte WT-1 marker in ANCA-associated glomerulonephritis is considered indicative of actual podocyte loss or at least, of a loss of functionality. Furthermore, our study indicates that podocyte foot process width at baseline could be indicative for proteinuria at short term follow up. For prognostic purposes, we therefore suggest to include a description of the foot process width in the diagnostic report of a biopsy with ANCA-associated glomerulonephritis.